Zalety i ograniczenia wykorzystania interaktywnych gier ruchowych (exergames) jako stymulatora aktywności fizycznej dzieci i młodzieży w czasie wolnym - Strugarek, Jan (Wydawnictwo Naukowe UAM, 2016)
The purpose of this article is to present possible uses of new interactive games, when the gamer must be obligatorily physically active. Playing a game, he is forced to have a good personal level of physical fitness, making him fit for the purpose of a game. Additionally, playing a game actively reduces the phenomenon of sedentary behavior in children and youth. Exergames appear to be a promising tool for the increase of the daily dose of movement in children and youth, which will affect the improvement of their physical and health condition.
Benefits and Limitations of Exergames as a Leisure Time Stimulator of Physical Activity of Children and Youth
Keywords: physical activity; interactive video games (exergames); physical education of children and youth; sedentary behavior